significant dose-response relationship emerging above roughly 150 IU/day, leading the authors to recommend that high-dosage Vitamin E be avoided. This is not a marginal caveat; it is a direct contradiction of the protective benefit that such products imply. The pattern extends well beyond a single nutrient. According to PubMed, a systematic review and meta-analysis spanning 884 randomized trials and more than 880,000 participants reported - KK, Mueen Ahmed (Free Radicals and Antioxidants, 2026)
Antioxidant dietary supplements continue to be marketed to the public with broad implications of disease prevention and “healthy aging,” yet the weight of randomized evidence has not kept pace with the confidence of the claims. I write to argue that this gap warrants closer regulatory attention to consumer-facing antioxidant messaging. According to PubMed, a meta-analysis of nineteen randomized trials involving nearly 136,000 participants found that high-dosage Vitamin E supplementation (≥400 IU/day) was associated with increased all-cause mortality, with a statistically significant dose-response relationship emerging above roughly 150 IU/day, leading the authors to recommend that high-dosage Vitamin E be avoided. This is not a marginal caveat; it is a direct contradiction of the protective benefit that such products imply. The pattern extends well beyond a single nutrient. According to PubMed, a systematic review and meta-analysis spanning 884 randomized trials and more than 880,000 participants reported that Vitamin C, Vitamin D, Vitamin E, and selenium showed no effect on cardiovascular disease or type 2 diabetes risk, while beta-carotene supplementation increased all-cause mortality, cardiovascular mortality, and stroke risk. The same analysis found benefit clustered narrowly around specific agents such as omega-3 fatty acids and folic acid rather than around generic antioxidant supplementation, underscoring that “antioxidant” is not a guarantee of benefit. The concern is one of consumer expectation. A label that foregrounds free-radical scavenging invites the inference that more is better and that the product prevents disease, an inference the trial literature does not support and in places actively contradicts. Where a credible body of high-quality evidence shows no benefit or net harm at the doses consumers commonly take, permitting open-ended structural or implied prevention claims is difficult to justify on public-health grounds. I am not arguing that micronutrients are irrelevant, nor that correcting a documented deficiency lacks value. I am arguing that the marketing of high-dose antioxidant supplements to healthy populations should be required to reflect the actual evidence, including its null and adverse findings. Clearer substantiation standards, and plain-language acknowledgment of trial outcomes, would help consumers make informed choices. The editorial and scientific community can advance this by consistently distinguishing deficiency correction from speculative prevention whenever these products are discussed.